Does poverty increase the risk of social isolation?: insights based on panel data from Germany - Eckhard, Jan (The sociological quarterly, 2018)
Sociological literature suggests a causal effect of poverty on the risk of social isolation. While previous research on this link is only based on cross-sectional data, this article presents more valid evidence for this assumption by applying fixed-effects regression methods and panel data (German Socio-economic Panel). First, the study shows that the poverty effect on isolation occurs regardless of time-constant unobserved heterogeneity. Second, it examines whether poverty and isolation are correlated because of a mutual association with critical life events (health deterioration, dissolutions of couple relationships, and job loss) that may increase both the risk for poverty and the risk for isolation. Regarding men, the effect of isolation on poverty is not attributable to the cited biographical transitions. Regarding women, it is only in part—but not in whole—attributable to dissolutions of couple relationships.